Gender in Germany and beyond exploring the legacy of Jean Quataert - Evans, Jennifer V. 1970-; Rose, Shelley (Berghahn, 2023)
"Jean Quataert redefined the boundaries of at least five historical fields including European socialism, women's history and gender history, and international law and human rights. In this volume dedicated to her pioneering work, established and emerging scholars showcase the signature ways in which Quataert, as one of the discipline's first women's historians, has influenced how subsequent generations think about history writing as a form of intellectual activism. Gender in Germany and Beyond presents cutting edge historiographical commentary alongside new work which address subjects such as the history of German colonialism and women's colonial leagues, human rights advocacy during the Cold War, and the complexities of turn of the century gay and lesbian rights organizing"--
Keywords: Geschichte 1871-2000; Feminismus; Frau; Deutschland; Quataert, Jean H. / (Jean Helen) / 1945- / Political and social views; Women / Germany / History; Feminism / Germany / History; Sex role / Germany / History; Women and socialism / Germany / History; Human rights / Germany; Feminism; Human rights; Political and social views; Sex role; Women; Women and socialism; Germany; History; Festschrift; Aufsatzsammlung